Infrapopliteal angioplasty using a combined angiosomal reperfusion strategy. - G K Ambler; A L Stimpson; B G Wardle; D C Bosanquet; U K Hanif; S Germain; C Chick; N Goyal; C P Twine (PLoS ONE, 2017)
Infra-popliteal angioplasty continues to be widely performed with minimal evidence to guide practice. Endovascular device selection is contentious and there is even uncertainty over which artery to treat for optimum reperfusion. Direct reperfusion (DR) targets the artery supplying the ischaemic tissue. Indirect reperfusion (IR) targets an artery supplying collaterals to the ischaemic area. Our unit practice for the last eight years has been to attempt to open all tibial arteries at the time of angioplasty. When successful, this results in both direct and indirect; or combined reperfusion (CR). The aim was to review the outcomes of CR and compare them with DR or IR alone.An eight year retrospective review from a single unit of all infra-popliteal angioplasties was undertaken. Wound healing, limb salvage, amputation-free and overall survival data as well as re-intervention rates were captured for all patients. Subgroup analysis for diabetics was undertaken. Kaplan Meier curves are presented for survival outcomes. All odds and hazard ratios (HR) and p values were corrected for bias from confounders using multivariate analysis.250 procedures were performed: 22 (9%) were CR; 115 (46%) DR and 113 (45%) IR. Amputation-free survival (HR 0.504, p = 0.039) and re-intervention and amputation-free survival (HR 0.414, p = 0.005) were significantly improved in patients undergoing CR compared to IR. Wound healing was similarly affected by reperfusion strategy (OR = 0.35, p = 0.047). Effects of CR over IR were similar when only diabetic patients were considered.Combined revascularisation can only be achieved in approximately 10% of patients. However, when successful, it results in significant improvements in wound healing and amputation-free survival over simple indirect reperfusion techniques.